2007
DOI: 10.1016/j.dnarep.2007.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between DNA polymerases β and λ in repair of oxidation DNA damage in chicken DT40 cells

Abstract: DNA polymerase λ (Pol λ) is a DNA polymerase β (Pol β)-like enzyme with both DNA synthetic and 5'-deoxyribose-5'-phosphate lyase domains. Resent biochemical studies implicated Pol λ as a backup enzyme to Pol ß in the mammalian base excision repair (BER) pathway. To examine the interrelationship between Pol λ and Pol ß in BER of DNA damage in living cells, we disrupted the genes for both enzymes either singly or in combination in the chicken DT40 cell line and then characterized BER phenotypes. Disruption of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 19 publications
3
53
0
Order By: Relevance
“…We conclude from these data that Pol ␤ can function independently of interaction with XRCC1 following oxidative DNA damage or, more likely, that another DNA polymerase can substitute for Pol ␤. For example, Pol , Pol , and Pol Q also are implicated in the cellular response to H 2 O 2 , and Pol Q has been reported to physically associate with XRCC1 (5,39,47,51,57). Alternatively, the long-patch repair DNA polymerases Pol ␦ and/or Pol ε might substitute for Pol ␤.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude from these data that Pol ␤ can function independently of interaction with XRCC1 following oxidative DNA damage or, more likely, that another DNA polymerase can substitute for Pol ␤. For example, Pol , Pol , and Pol Q also are implicated in the cellular response to H 2 O 2 , and Pol Q has been reported to physically associate with XRCC1 (5,39,47,51,57). Alternatively, the long-patch repair DNA polymerases Pol ␦ and/or Pol ε might substitute for Pol ␤.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we compared the activities of DNA pol and DNA pol ␤, the 2 major SP-BER pols (22)(23), and showed that both DNA pol and DNA pol ␤ physically interact with RP-A (Fig. 2F), which, together with PCNA, reduced the efficiency of gap-filling by DNA pol ␤ in the presence of an 8-oxo-G lesion (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…All DT40 mutants were derived from isogenic DT40 parent cell lines (Supplementary Table S1). The DT40 cells and their mutants were cultured as previously reported (8). Parental colorectal cancer cell lines (RKO) cells and isogenic clones harboring an engineered disruption of FANCC or FANCG (9) were cultured in a humidified 5% CO 2 atmosphere at 37jC.…”
Section: Methodsmentioning
confidence: 99%